Overfunding and Signaling Effects of Herding Behavior in Crowdfunding - Svatopluk Kapounek; Zuzana Kucerová (Center for Economic Studies and ifo Institute (CESifo), 2019)
The paper employs a dynamic market-wide herding behavior measure of 117,166 lending-based campaigns in 119 online platforms in 37 countries that explores whether lenders follow each other in the whole crowdfunding market, within the groups of top platforms, within the specific category or platform, and within the specific category in the specific platform. We show that herding behavior plays an important signaling role in reducing opportunity costs if the auction does not receive enough monetary bids. Additionally, our threshold models identify significant herding behavior after funding goals are raised and highlight the controversial effects of signaling mechanisms on adverse selection in crowdfunding markets.
Keywords: C55; D26; G21; 330; asymmetric information; crowdfunding; herding behavior; overfunding; peer-to-peer lending; signaling